2003
DOI: 10.1002/ijc.11594
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carcinoma cell invasion by protein C inhibitor whose expression is decreased in renal cell carcinoma

Abstract: Protein C inhibitor (PCI), a member of the serine protease inhibitor family, is produced in various human tissues, including the liver, kidney and testis. In addition to inhibiting the anticoagulant protein C pathway, PCI also inhibits urinary plasminogen activator (uPA), which is a well-known mediator of tumor cell invasion. In the present study, to clarify the biologic significance of PCI in the kidney, we compared the expression of PCI between human renal cell carcinoma (RCC) tissue and nontumor kidney tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…This is supported by results showing that Caki-1 cells exhibit lower invasive capacity when uPA activity is reduced by added anti-uPA antibody and PAI-1. 31 Interestingly, an in vivo assay with another FTI, L-744,832, also showed inhibition of growth of 3 human prostate tumor xenographs in nude mice. 42 High levels of plasminogen activators as well as MMP-2 and MMP-9 have been correlated with aggressive phenotypes in different cancers, including prostate 27 and renal 43 cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by results showing that Caki-1 cells exhibit lower invasive capacity when uPA activity is reduced by added anti-uPA antibody and PAI-1. 31 Interestingly, an in vivo assay with another FTI, L-744,832, also showed inhibition of growth of 3 human prostate tumor xenographs in nude mice. 42 High levels of plasminogen activators as well as MMP-2 and MMP-9 have been correlated with aggressive phenotypes in different cancers, including prostate 27 and renal 43 cancers.…”
Section: Discussionmentioning
confidence: 99%
“…30 The in vitro invasiveness of renal cancer Caki-1 cells, which express uPA, was significantly enhanced by addition of uPA but inhibited by antiuPA antibody and PAI-1. 31 Together, these data suggested that prostate PC-3 and renal Caki-1 cancer cells could be excellent models for investigating the ability of SCH-66336 to regulate the expression and activity of gelatinases and of components of the plasminogen activation system.…”
mentioning
confidence: 90%
“…14 Palmieri et al showed that adhesion to extracellular matrix proteins such as fibronectin, vitronectin, and laminin is increased in breast cancer cells overexpressing PCI as compared to control cells; this effect appears to be partially mediated by integrin, whose expression is also enhanced in PCI-expressing breast cancer cells as compared to mock-transfected cells. 15 On the other hand, we demonstrated that PCI expression is significantly decreased in the RPTEC-derived renal carcinoma cell line, Caki-1 cells, and that PCI inhibits in vitro the Matrigel invasion of renal carcinoma cells by inhibiting uPA 16 ; however, we could not evaluate the effect of PCI on tumor metastasis in vivo because Caki-1 cells were not able to grow even in severe combined immunodeficient (SCID) mice. 16 Therefore, it remains still unclear whether PCI is able to regulate in vivo the metastatic activity of tumor cells.…”
mentioning
confidence: 92%
“…15 On the other hand, we demonstrated that PCI expression is significantly decreased in the RPTEC-derived renal carcinoma cell line, Caki-1 cells, and that PCI inhibits in vitro the Matrigel invasion of renal carcinoma cells by inhibiting uPA 16 ; however, we could not evaluate the effect of PCI on tumor metastasis in vivo because Caki-1 cells were not able to grow even in severe combined immunodeficient (SCID) mice. 16 Therefore, it remains still unclear whether PCI is able to regulate in vivo the metastatic activity of tumor cells.In the present study, we investigated (i) the effect of recombinant intact PCI, reactive site-modified (Arg354 to Ala) PCI (R354APCI), or N-terminal fragment of protease-cleaved PCI (NTPCI), on the in vitro invasiveness of MDA-231 cells, (ii) the in vitro invasiveness of MDA-231 breast cancer cells expressing intact PCI, R354APCI or NTPCI, and (iii) the growth and metastatic potential of intact PCI, R354APCI, or NTPCI-expressing MDA-231 cells. In addition, we investigated the effect of intact PCI, R354APCI, or NTPCI on angiogenesis, which is known to be important for tumor growth and metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation